Case report: A hybrid technique for a safe nephrectomy in a giant kidney angiomyolipoma - Vento, Vincenzo; Galosi, Andrea Benedetto; Ranghino, Andrea; Montecchiani, Luca; Felici, Luca; Loggi, Silvia; Cerutti, Elisabetta; Milanese, Giulio; Franzese, Carmine; Castellani, Daniele; Gatta, Emanuele (Frontiers in Surgery, 2022)
Background Giant angiomyolipoma is usually associated with genetic syndromes and complications (spontaneous rupture and bleeding, hematuria, hypertension) and mass-related symptoms (flank and abdominal pain). Case presentation We present a case of a 20-year-old woman suffering from tuberous sclerosis who was referred to our hospital with a giant angiomyolipoma causing abdominal pain. A contrast-enhanced computed tomography showed a left angiomyolipoma, measuring 28 cm × 17 cm × 27 cm. After a multidisciplinary team discussion, the patient was submitted for a nephrectomy. Percutaneous temporary occlusion of the main renal artery was achieved through an endovascular balloon catheter. Through the balloon catheter guidewire, 2,500 IU of heparin was infused to reduce the risk of tumor vein thrombosis and venous embolism. This allowed a safe kidney manipulation through a left thoracoabdominal approach. The postoperative course was uneventful. Pathology showed a 40 cm × 30 cm × 9 cm and 10 kg AML. One year after surgery, the patient is on follow-up, and her estimated glomerular filtration is 120.5 ml/min/1.73 m2. Conclusion The present case showed that the endovascular control of the main renal artery could be considered a useful approach to safely managing huge renal masses when renal hilar control is expected to be very difficult.